Decentralization and tax independence in OECD countries: GDP per capita analysis from 1995–2018 - Anna Semmerling; Andrzej Paczoski; Giuseppe T. Cirella (Journal of Banking and Financial Economics)
The association of local and regional self-government is examined in regard to the decentralization of state administration. This study extrapolated data from 36 Organisation for Economic Cooperation and Development (OECD) countries and analyzed whether decentralization of the state assists in economic growth and development. Administrative decentralization is explored through defining a precedence from the literature. A systematic literature review was conducted and macroeconomic OECD data using nominal gross domestic product was analyzed for the period of 1995–2018. The results confirmed that decentralization does not positively correlate with the level of tax independence of local government and, in effect, is not an advantage. Territorial administration is highlighted throughout the paper as a key factor behind tax autonomy in relation to fiscal decentralization levels.